2021
DOI: 10.9734/ijpss/2021/v33i2030642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bioslurry from Fixed Dome and Tubular (Flexi) Biodigesters on Selected Soil Chemical Properties, Maize (Zea mays) Growth, Yield and Quality

Abstract: Agricultural utilization of bioslurry plays a critical role in soil conditioning and hence crop production. It also reduces greenhouse gas emissions thus mitigating climate change. Although the effect of bioslurry on growth and yields is well researched, that of different biodigester types is under-researched. Therefore, a study was carried out in Waruhiu Agricultural Training Centre, Githunguri sub-county, Kiambu county in Kenya, to investigate the effect of bioslurry from flexi and dome biodigesters on soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…While Nitrogen plays crucial role in vegetative growth, phosphorus is key in germination and root formation [40,41] promoting new cells development, plant vigour, leaves and height. This finding concur with Aslam et al [50] who reported increased plant height and number of green gram branches on application of inorganic fertilizers and Rewe et al [51] who reported increased maize height and number of leaves on combined application of slurry and inorganic fertilizer.…”
Section: Plant Heightsupporting
confidence: 91%
See 1 more Smart Citation
“…While Nitrogen plays crucial role in vegetative growth, phosphorus is key in germination and root formation [40,41] promoting new cells development, plant vigour, leaves and height. This finding concur with Aslam et al [50] who reported increased plant height and number of green gram branches on application of inorganic fertilizers and Rewe et al [51] who reported increased maize height and number of leaves on combined application of slurry and inorganic fertilizer.…”
Section: Plant Heightsupporting
confidence: 91%
“…Continuous decomposition and mineralization of organic matter can also avail more mineral Phosphorus in soil solution or buffer soil pH promoting Phosphorus release from colloidal structures [40][41][42]. Additionally, the organic matter presence can avail more P in soil solution by reducing P chelation by lowering the activities of the polyvalent cations such as Ca, Al and Fe that form insoluble salts with P [43,44].…”
Section: Effects Of Farmyard Manure And/or Mineral Fertilizer In Prop...mentioning
confidence: 99%
“…Correspondingly, the additive effect on nutrient supply and improvement of soil physical conditions, checks N losses and conserves soil N by forming organic-mineral complexes, thus ensuring continuous N availability [24]. This results collaborate findings by [19,25,26,27,28,29,30]. Nodule formation was not significantly affected by application of either manure or fertilizer in this post mined soils.…”
Section: Green Gram Growth and Yield As Affected By Manure And Inorga...supporting
confidence: 86%
“…This phenomenon can be attributed to synergistic effect of manure and fertilizer on on soils. While inorganic fertilizer supplies applied nutrients in readily available forms and quantities within the exchange complex for plant uptake, manure on the other hand support sustainable nutrient availability through promotion of aggregate stability, temperature regulation, water and nutrient holding capacity and biological activities such as decomposition and mineralization [18,19,20,21]. The synergy improves root penetration, nutrient uptake and favorable environment within the rhizosphere leading to improved plant growth that entails leaf numbers, LAI, leaf length, plant height and stem circumference [20,21,22].…”
Section: Effects Of Inorganic Fertilizer On Crop Development and Yieldmentioning
confidence: 99%
“…While inorganic fertilizer supplies applied nutrients in readily available forms and quantities within the exchange complex for plant uptake, manure on the other hand support sustainable nutrient availability through promotion of aggregate stability, temperature regulation, water and nutrient holding capacity and biological activities such as decomposition and mineralization [18,19,20,21]. The synergy improves root penetration, nutrient uptake and favorable environment within the rhizosphere leading to improved plant growth that entails leaf numbers, LAI, leaf length, plant height and stem circumference [20,21,22]. As the key food manufacturing organ through photosynthesis, increased leaf numbers, length and LAI indicate greater production and translocation of assimilates to other parts of the plant leading to improved root development, biochemical processes, plant height, dry matter accumulation and grain yield [23,24].…”
Section: Effects Of Inorganic Fertilizer On Crop Development and Yieldmentioning
confidence: 99%